Fractal dimension for fractal structures : with applications to finance /: with applications to finance. ([2019]) - Fernández-Martínez, Manuel; García Guirao, Juan Luis; Sánchez-Granero, Miguel Ángel; Trinidad Segovia, Juan Evangelista
No abstract available